Rice Husk-Activated Carbon as Adsorben in Agricultural Wastewater - Daning Kinanti Sutama; Aulia Firda Alfiana; Nabilatul Choir (Prodi Ilmu Lingkungan Fakultas Sains dan Teknologi, 2025)
Rice husk is an agricultural by-product rich in organic matter, and improper management can cause environmental pollution. Given the high carbon content in rice husk, it can be used as an adsorbent. Furthermore, the type of activator and activation technique employed impact the properties of activated carbon. Due to its ability to produce activated carbon with a high pore volume and specific surface area, Pottasium hydroxide is a chemical substance that is frequently employed. This study sought to ascertain whether rice husks might be used as activated carbon to lower the amount of organic matter in liquid effluent from the agricultural wastewater. The results of this study indicate that rice husk activated carbon can reduce the level of TDS by 86%, TSS by 53,85%, and pH 6 from the initial level. The data suggests that the 1:110 adsorbent-to-adsorbate ratio is the most effective in reducing TDS concentrations in tofu wastewater, providing a steady and significant decrease in TDS over time. In comparison, the 1:120 ratio shows a similar trend but with less efficiency, while the 1:130 and 1:140 ratios show less consistent and slower reductions in TDS. Therefore, the 1:110 ratio should be considered optimal for TDS removal in this study. Further optimization of the adsorption process may help improve the efficiency of higher adsorbent-to-adsorbate ratios. The data suggests that lower adsorbent-to-adsorbate ratios (particularly 1:110 and 1:120) are more effective in reducing TSS in tofu wastewater, with the 1:110 ratio providing the best results in terms of adsorption efficiency. However, further analysis may be required to determine the optimal time and ratio for the highest efficiency in the adsorption process. In this study, the normal pH value was obtained, namely 6. So, the results of pH measurement of the sample did not affect the adsorption process.